RESPONCE OF SOYBEAN PLANT (Glycine max (L.) Mer) ON EFFICIENCY USE OF NPK FERTILIZER WITH ADDITION OF ORGANIC FERTILIZER - Moch Arifin; Juli Santoso; Indriani Prasetyaningsih Ardie (UNEJ e-Proceeding, 2017)
Soybean is one of multipurpose plant because soybean can be used as food, as feedingredients, as well as for raw materials of various manufacturing and processed industries.In Indonesia the average requirement of soybean every year reaches 2-3 million tons, whilethe national production of Indonesia only reached 870,068 tons (37.85% of domestic needs).According to the Central Bureau of Statistics (BPS) (2015) recorded imports of soybeansreached 1,525,748 tons. To achieve the target soybean production can be done with nonorganic fertilization. But this agricultural technology is not environmentally friendly becauseof the deposition of heavy metal elements that can pollute the environment. To avoiddeposition of heavy metal elements can be done addition of organic fertilizer. The purpose ofthis research is to know the responce of soybean plant to the efficiency of NPK fertilizer usewith the addition of organic fertilizer. The research method is a simple experiment using randomized block design with theaddition of organic fertilizer that is P0: NPK 100% (Control), P1: NPK 75% + 30 ton/haorganic fertilizer, P2: NPK 50% + 30 ton/ha organic fertilizer, P3: NPK 25% + 30 ton/haorganic fertilizer, P4: organic fertilizer 30 ton/ha and repeated 3 times. The result of observation of plant pod number, number of planting seeds, number ofroot nodule, dry weight of soybean tends, with high clay C-organic content to be moreresponce to the use of NPK 25% fertilizer showed higher tendency with production perhectare (= 2.17 ton/ha) higher than other treatment. It can be said also that with the use ofNPK fertilizer 25% more efficiency.